Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.1002/pola.1990.080280723
|View full text |Cite
|
Sign up to set email alerts
|

Grafting of polyesters from ultrafine inorganic particles: Copolymerization of epoxides with cyclic acid anhydrides initiated by COOK groups introduced onto the surface

Abstract: The grafting of polyesters onto ultrafine inorganic particles, such as silica, titanium oxide, and ferrite, by use of potassium carboxylate (COOK) groups introduced onto the surface was investigated. The introduction of COOK groups onto the surface was achieved by the neutralization of acid anhydride groups, which were introduced by the reaction of 4‐trimethoxysilyltetra‐hydrophthalic anhydride with hydroxy groups on the surface: the amount of COOK groups introduced onto the surface of silica, titanium oxide, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
37
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 11 publications
0
37
0
Order By: Relevance
“…We also reported that potassium carboxylate groups introduced onto ultrafine particles have ability to initiate the anionic ring-opening alternating polymerization of epoxides with cyclic acid anhydrides and the corresponding polymer, i.e., polyester, was grafted onto these surfaces. 5 Furthermore, lithium silanolate groups introduced onto silica surface were capable of initiating anionic graft polymerization of methyl methacrylate and cyclic siloxanes. 6 Cationic graft polymerization of polymers onto ultrafine silica has never been reported.…”
mentioning
confidence: 99%
“…We also reported that potassium carboxylate groups introduced onto ultrafine particles have ability to initiate the anionic ring-opening alternating polymerization of epoxides with cyclic acid anhydrides and the corresponding polymer, i.e., polyester, was grafted onto these surfaces. 5 Furthermore, lithium silanolate groups introduced onto silica surface were capable of initiating anionic graft polymerization of methyl methacrylate and cyclic siloxanes. 6 Cationic graft polymerization of polymers onto ultrafine silica has never been reported.…”
mentioning
confidence: 99%
“…5 Polymer-grafted silica (1.0 g) was dispersed in 100 cm 3 of tetrahydrofuran with a magnetic stirrer, and the dispersion was allowed to stand at room temperature. After a prescribed time, 5.0 cm 3 of dispersion liquid was taken out with a pipet, dried in vacuo, and the residual silica particles were weighed.…”
Section: Dispersibility Of Polymer-grafted Silicamentioning
confidence: 99%
“…1 • 2 In a series of papers, we reported the grafting of polymers onto these ultrafine particles initiated by surface azo, 3 peroxide,4 potassium carboxylate, 5 and acylium perchlorate 6 groups. During these polymerizations, polymer-grafted ultrafine particles with a higher percentage of grafting were successfully obtained through the propagation of polymer chains from the particle surface.…”
mentioning
confidence: 99%
“…[1][2][3][4][5] We have reported the surface initiated graft polymerization of various monomers onto silica nanoparticle by using previously introduced initiating groups on the surface, such as azo 6 and peroxyester, 7 acylium perchlorate, 8 and potassium carboxylate. 9 In addition, we have reported that hyperbranched poly-(amidoamine) (PAMAM) can be grown from amino groups on silica nanoparticles, 10 chitosan powder, 11 and carbon black 12 surfaces using dendrimer synthesis methodology ( Figure 1). Grafting was achieved by repeating the following two processes in methanol [10][11][12] and in solvent-free dry-system: 13 (1) Michael addition of amino groups on the surface to methyl acrylate (MA), and (2) amidation of the resulting terminal methyl ester groups with ethylenediamine (EDA).…”
mentioning
confidence: 99%